The Influence of Ewom and Fear of Missing Out in the Intention to Buy Skincare Products Through Tiktok - Tutut Ardianti; Joel Faruk Sofyan (Publikasi Indonesia, 2024)
The current social media platform provide a variety of social content that raises new phenomena to become viral and beauty content is one of the most popular content. This study examines the influence of eWOM and Fear of Missing Out (FOMO) in the purchase intention of Skintific skincare products through TikTok. To understand the influence of eWOM, this study combines the information adoption model with self-determination theory as a theoretical basis. Data collection was conducted by an online survey with a purposive sampling method using 235 selected respondents. The data was then processed by applying PLS-SEM to test the proposed hypotheses. The findings show that information usefulness has a positive effect on information adoption, information adoption and FOMO have a positive effect on purchase intention, information credibility and information quantity have a positive effect on information usefulness, and information quality has no significant effect on information usefulness. The direct managerial implication of this finding be a valuable addition to the academic understanding of FOMO in the information adoption model and provide direction for companies in formulating digital marketing designs that focus on the credibility and frequency of content broadcast to provoke consumer desire to use the company's products so as not to be left behind by others.